Contractile effects of stimulation of D1-dopamine receptors in the isolated human atrium - U. Gergs; T. H. Pham; L. M. Rayo Abella; C. Hesse; P. Grundig; S. Dhein; B. Hofmann; J. Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Dopamine receptors have been claimed not to directly increase contractility in the human heart. Therefore, we performed contraction experiments in isolated electrically driven human atrial preparations (HAP). For comparison, we performed contraction experiments with left atrial preparations of transgenic mice which harbor a cardiac overexpression of human D 1 -dopamine receptors (D 1 -TG). In D 1 -TG, first we noted that dopamine (10 nM–10 µM cumulatively applied) in the presence of propranolol exerted a concentration- and time-dependent positive inotropic effect in D 1 -TG. In a similar fashion, dopamine increased force of contraction in the presence of 0.4 µM propranolol in HAP and these effects were amplified by pre-treatment with inhibitor of phosphodiesterase III (1 µM) cilostamide. Moreover, contractile effects of dopamine in the presence of propranolol 0.4 µM in HAP were antagonized by odapipam, haloperidol, or raclopride. Ten micromolars of fenoldopam in the presence of cilostamide increased force of contraction in HAP and this effect was antagonized by SCH 23390. We conclude that stimulation of human D 1 -dopamine receptors can increase force of contraction in the HAP.